Evaluation of Nurses knowledge about De- escalation Strategies to Dealing with an Aggressive Inpatient at Psychiatric Hospital - Abdulla, Mohammed; Mohammed, Saja Hashem (International Journal of Psychosocial Rehabilitation, 2020)
Background: In psychiatric hospital sometimes there is risk or dangerous for nurse or the other medical team , the aggressive patient verbally or non-verbally may hurt if didn’t calm him or de-escalated , our nurses may have a low knowledge for managing aggressive patients in our psychiatric hospitals and did not know how to deal with them, knowledge for these strategies need to evaluated. Objectives: The study objective is to assess nurse’s knowledge about De-escalation Strategies for dealing with an Aggressive Inpatient at Al-Rashad Psychiatric Hospital. Materials and Method: A descriptive study was conducted for the period from 9 July 2019 to 18 July 2019. A probability sampling using randomized controlled trial (RCT) design, the sample consisted of (50) nurses who were working at Al-Rashad Psychiatric Training Hospital in Baghdad . Data were collected by using constructed questionnaire after validity and reliability of it were estimated. Reliability of the questionnaire was estimated through a pilot study and the validity was submitted through (15) experts related in the field of study. Data were collected through an interview approach. Data were analyzed throughout using of descriptive and inferential statistical analysis test using SPSS Version-26. Results: Findings of current study indicates low level of nurses’ knowledge about De-escalation Strategies used for dealing with an aggressive patient. Conclusion: The study concludes that there was a considerable lack in nurses’ knowledge concerning De- escalation Strategies to deal with an aggressive psychiatric patient. Recommendations: The study recommends that there is an important need for educated and trained the nurses in psychiatric ward especially who have lack of knowledge and skills about De-escalation Strategies to deal with violence of psychiatric patients.